Present and future of primary level Science Education: the experiences of Mobilis Science Centre - Rákosi, Szabolcs; Dőry, Tibor (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2022)
The breakthrough of science, technology and the growing importance of 21st century skills are radically transforming not only our work, but our daily lives as well. In the long term, STEM career orientation and, in a broader sense, the entire education system play a key role in the availability of well-qualified, motivated workforce. In this paper, results of scientific and technical career guidance in Europe and Hungary are presented, through the analysis of public databases.The study is based on the processing of domestic and international literature and public databases. After that, as a result of personal data collection of the authors, a promising practice is presented in detail, as well as the limitations of its transferability. The main goal of this paper is to present this bottom-up initiative that can be suitable for supplementing and supporting education of its area. The results indicate that science centres can provide exceptional support for public education and some of their activities may even represent the future of science education. This study contributes to the ongoing social discourse on the future of public education and career guidance through the examination of significant challenges of education and the detailed presentation of an initiative that can provide a solution to some of them.